Exploring the Potential Roles of Band 3 and Aquaporin-1 in Blood CO2 Transport–Inspired by Comparative Studies of Glycophorin B-A-B Hybrid Protein GP.Mur - Hsu, Kate (Frontiers in Physiology, 2018)
The Cl—/HCO3— exchanger band 3 is functionally relevant to blood CO2 transport. Band 3 is the most abundant membrane protein in human red blood cells (RBCs). Our understanding of its physiological functions mainly came from clinical cases associated with band 3 mutations. Severe reduction in band 3 expression affects blood HCO3—/CO2 metabolism. What could happen physiologically if band 3 expression is elevated instead? In some areas of Southeast Asia, about 1–10% of the populations express GP.Mur, a glycophorin B-A-B hybrid membrane protein important in the field of transfusion medicine. GP.Mur functions to promote band 3 expression, and GP.Mur red cells can be deemed as a naturally occurred model for higher band 3 expression. This review first compares the functional consequences of band 3 at different levels, and suggests a critical role of band 3 in postnatal CO2 respiration. The second part of the review explores the transport of water, which is the other substrate for intra-erythrocytic CO2/HCO3— conversion (an essential step in blood CO2 transport). Despite that water is considered unlimited physiologically, it is unclear whether water channel aquaporin-1 (AQP1) abundantly expressed in RBCs is functionally involved in CO2 transport. Research in this area is complicated by the fact that the H2O/CO2-transporting function of AQP1 is replaceable by other erythrocyte channels/transporters (e.g., UT-B/GLUT1 for H2O; RhAG for CO2). Recently, using carbonic anhydrase II (CAII)-filled erythrocyte vesicles, AQP1 has been demonstrated to transport water for the CAII-mediated reaction, CO2(g) + H2O ⇌ HCO3—(aq) + H+(aq). AQP1 is structurally associated with some population of band 3 complexes on the erythrocyte membrane in an osmotically responsive fashion. The current findings reveal transient interaction among components within the band 3-central, CO2-transport metabolon (AQP1, band 3, CAII and deoxygenated hemoglobin). Their dynamic interaction is envisioned to facilitate blood CO2 respiration, in the presence of constantly changing osmotic and hemodynamic stresses during circulation.